FREQUENCY OF PULMONARY HYPERTENSION IN CASES OF INTERSTITIAL LUNG DISEASE: CROSS-SECTIONAL STUDY - SHAH, Z; SANAULLAH, .; ASLAM, S; KHAN, MA; BUSHRA, A (Biological and Clinical Sciences Research Journal, 2024)
Pulmonary hypertension (PH) is a significant complication of interstitial lung disease (ILD), often contributing to increased morbidity and mortality. Understanding the prevalence and associated risk factors of PH in ILD patients can aid in early detection and tailored management strategies. Objective: .To determine the frequency of pulmonary hypertension in patients with interstitial lung disease. Methods: A cross-sectional study was conducted on 200 patients diagnosed with ILD. Data on demographics, clinical characteristics, smoking history, and comorbidities were collected. Pulmonary hypertension was screened using transthoracic echocardiography, defined as a mean pulmonary artery pressure (mPAP) ≥ 20 mmHg. Statistical analyses were performed to assess associations between PH and patient characteristics. Results: Pulmonary hypertension was observed in 23.5% of the study population. The mean age of participants was 50.63 ± 12.03 years, with a male predominance (56%). Smoking was significantly associated with PH (p = 0.01), with 44.7% of smokers exhibiting PH. Hypertension was common (59.0%) but showed no significant association with PH. No significant differences in PH prevalence were observed based on place of residence or employment status. Conclusion: Pulmonary hypertension is a prevalent complication in ILD, particularly among smokers and males. Routine screening for PH in ILD patients, especially those with known risk factors, is essential for early diagnosis and intervention. These findings emphasize the need for targeted management strategies to mitigate the impact of PH on this vulnerable population.